Redesain Dan Restrukturisasi Organisasi ; Upaya Perbaikan Kinerja Organisasi - M. Adi Trisna Wahyudi; M. Syam’un Rosyadi; Kusnul Ciptanila Yuni K; Nizar Zakaria; M. Zulfa ‘Ulumuddin Alwy; Anita Musfiroh (Universitas Muhammadiyah Jember, 2024)
This community service program aims to improve the performance of village youth organizations through organizational redesign and restructuring. This activity was motivated by various problems faced by village youth organizations, such as ineffective organizational structures, lack of clear division of tasks, and minimal member participation. Through a participatory and collaborative approach, this program involves all members of the organization in the process of assessing needs, planning and implementing change. The first step is to conduct an in-depth analysis of the existing organizational structure and identify weaknesses and potential improvements. Based on the results of this analysis, a redesign of the organizational structure was carried out with the aim of creating a more efficient and effective work flow. Apart from that, various restructuring strategies were also implemented, such as a more specific division of tasks, increasing leadership capacity, and developing better communication mechanisms. The results of this activity show a significant increase in the performance of village youth organizations, which is reflected in increased member participation, effectiveness of program implementation, and achievement of overall organizational goals. It is hoped that this program can become a model for other youth organizations in efforts to improve performance through organizational redesign and restructuring.